Association of Pulmonary Valve Morphology Differences With Outcomes in Tetralogy of Fallot Repair With Right Ventricular Outflow Tract Incision - Liu, Jinyang; Jiang, Xianchao; Peng, Bo; Li, Shoujun; Yan, Jun; Wang, Qiang; Liu, Zhimin (Frontiers in Cardiovascular Medicine, 2021)
Background: Current observational studies may not have large samples to investigate the relationship between pulmonary valve (PV) morphology differences and outcomes after complete repair for tetralogy of Fallot (TOF) by right ventricular outflow tract (RVOT) incision. This study aimed to assess the impact of PV morphology differences on outcomes after complete repair for TOF. Methods: This is a retrospective cohort study. Consecutive patients who underwent TOF repair with RVOT incision at Fuwai Hospital from January 2012 to December 2017 were included and compared according to PV morphology differences (unicuspid or bicuspid was abnormal morphology, while the tricuspid valve was normal morphology). The primary outcome was defined as a composite of death, or reintervention, or significant annular peak gradient (APG), or significant pulmonary regurgitation (PR), whichever occurred first. Multivariable Cox model analysis was used to assess the relationships between PV morphology differences and outcomes. Subgroup analysis and Propensity-score analysis were performed as sensitivity analyses to assess the robustness of our results. Results: The cohort included a total of 1861 patients with primary diagnosis of TOF, with 1688 undergoing CR-TOF with RVOT incision. The median age was 318 days (interquartile range [IQR]: 223-534 days), a median weight of 8.9 kg (IQR: 7.6-10.5 kg) and 60.0% (1011) were male. Complete follow-up data were available for 1673 CR-TOF patients with a median follow-up duration of 49 months. Adjusted risks for the primary outcome and significant APG were lower for patients with normal PV morphology at follow up (adjusted hazard ratio [HR]: 0.68; 95% CI: 0.46 to 0.98; adjusted HR: 0.22; 95% CI: 0.07 to 0.71, respectively). The trend for the primary outcome during follow-up remained unchanged, even in subgroups and propensity score matching analyses. Conclusions: In this analysis of data from a large TOF cohort, patients with normal tricuspid PVs were associated with a decreased risk of the primary outcome and a lower risk of significant APG, as compared with patients with abnormal unicuspid or bicuspid PVs.